Role of Institutional Quality and Financial Developments in Realizing Clean Energy Legislation in Indonesia - Supriyadi, Supriyadi; Sohag, Kazi; Yuniawan, Dani; Cahyaningsih, Diyah Sukanti; Chandrarin, Grahita; Mochtar, Dewi Astutty (International Journal of Energy Economics and Policy, 2024)
This study examines the intersection of financial markets and institutional quality (IQ) in enhancing clean energy production and access in Indonesia, a country that has placed a strong emphasis on renewable energy (RE) through its legislative framework. Utilizing various econometric methods, including Dynamic and fully-modified ordinary least squares (OLS), and dynamic simulated autoregressive distributed lag (ARDL) models, we analyze time series data from 1996 to 2022. The outcomes underscore the pivotal role of IQ (encompassing indicators like control of corruption, rule of law, regulatory quality, government effectiveness, political stability, and voice & accountability) in fostering the adoption of RE sources and broadening the reach of clean cooking energy. Although the impact of financial markets in isolation yields inconclusive findings, their intersection with IQ consistently bolsters Indonesia’s transition towards clean energy. This study puts forth various practical implications for policymakers seeking to bolster the efficacy of clean energy policies.